Why Doers Do—Part 1: Internal Elements of Human Performance. Issue 2 (February 2014) - Wile, David E.
<x xml:space="preserve">Abstract</x> The externality‐tangibility (E‐T) model of human performance is a human performance technology (HPT) model that categorizes nine all‐inclusive elements of HPT into families of elements that can be external or internal to a performer and tangible or intangible. This first installment of three looks at the internal factors: talents and skills or knowledge.